OP0130 Unique ultrasonographic findings in patients with the hereditary inclusion body myopathy. (1st June 2001) - Garofalo, GM; Adler, R; Darvish, D; Rafii, S; Paget, S; Kagen, L
Abstract : Background: Hereditary Inclusion Body Myopathy (HIBM) is an autosomal recessive disorder characterised histologically by the presence of beta amyloid fibrils in myofibers and clinically by muscle weakness and atrophy with quadriceps sparing. This disorder is seen in different ethnic groups including members of Iranian Jewish families where it has been mapped to chromosome 9p1-q1. The onset is usually in the 2nd to 3rd decade of life, with slow progression leading to severe involvement of multiple muscle groups, ultimately resulting in immobilisation. Objectives: To demonstrate the facility of the use of grey scale and power Doppler sonography as a non-invasive diagnostic procedure in the evaluation of HIBM. Methods: We studied 4 Iranian Jewish patients diagnosed with HIBM. Ultrasonographic examinations of the quadriceps femoris and hamstring muscle groups were carried out in these patients. Echogenicity, as determined by grey scale assessment, was used to detect disordered muscle structure and atrophy, and power Doppler sonography was used to assess vascularity. Results: The initial symptom in all was "footdrop" due to anterior tibial muscle weakness. Two patients with disease duration of seven years developed pelvic girdle and shoulder girdle weakness. Two patients with twenty-eight years of disease were restricted to wheelchairs with severe myopathy of the upper and lower extremities. All had significant family histories consistent with HIBM. An unusual and unique pattern of central atrophy of muscle with peripheral sparing was observed in all four patients. Vascularity was markedly reduced in the affected areas with relatively increased blood flow in the peripherally-spared areas. We referred to this as a "fried-egg" or "bull's eye" appearance. Conclusion: Our study demonstrates the use of both grey scale and power Doppler sonography as a helpful non-invasive procedure in the evaluation of HIBM. Their ability to define a unique centrifugal, "fried-egg" myopatic abnormality may be diagnostic for this disorder.